ANALISIS PENGARUH DIMENSI KOMITMEN ORGANISASI (AFFECTIVE, CONTINUANCE, NORMATIVE) TERHADAP KINERJA KARYAWAN - Nurofi, Achmad (STIE Totalwin Semarang, 2013)
This research analyzes the influences of organizational commitment to employee performance. Respondents of this research are 130 Respondent are production staff in XYZ firm Semarang. This research use Structural Equitation Modeling (SEM) under AMOS 21 program as analysis toolsThe model of relationship between the three variables studied shown that the organizational commitment that comprise of affective commitment, continuance commitment, have a significant effect on employeeâs performance with positive signs. The studied also shown that normatif commitment, have no significant effect on employeeâs performance.